الصّورة الحسّيّة في شعر السّريّ الرّفّاء (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
الحسّ واحد من أهمّ مكوّنات الصّورة الفنّيّة، والبحث ينطوي على دراسة هذا المكوّن الأساس للصّورة من خلال تحليل البناء الشّعريّ والكشف عن عناصره ، مبيّناً آراء النّقّاد فيه، وانطوى البحث على دراسة الصّورة الحسّيّة عند السّريّ الرّفّاء وقد تفاوتتْ تبعاً للعوامل المؤثّرة فيها، وتنوّعت بين الصّورة الحركيّة، والسّكونيّة، واللونيّة التي عكست صورة الواقع من خلال تقنيّات الفنّ  والجمال، والتّوازن والتّنسيق، فخرجت في ثيابٍ جديدةٍ من التّصوير الممتع. وقد أظهر البحث إسهام الصّورة الحسّيّة في الكشف عن الحقيقة وتعميقها، وفي التنفيس الشّخصيّ عن نفس مبدعها، وفي عكس المشكلات الاجتماعيّة التي كان ينبض بها عصر الشّاعر . ويصل البحث إلى أنّ الشّاعر استطاع أن يخلّص اللون من كونه مجرّد انطباعٍ حسّيّ، ومن رؤيته الانعزاليّة حيث وضع له وظيفته داخل نطاق الكلّ العامّ فلا ينظر إليه في ذاته، ولا يحكم عليه حكماً استقلاليّاً ، فتحوّل من عنصرٍ من عناصر الشّكل إلى عنصرٍ من عناصر المعنى، ومن وضعه التّزيينيّ كحلية للزّركشة إلى وضعه الشّعوريّ كأداة للتّعبير. Sense is one of the most important components of artistic image. This paper studies this element through analysing poetic construction and through exposing its elements and simultaneously showing critics views about it. This paper deals with studying the sense image in AlSeriAlRafaa poetry. This sense image fluctuates as per the elements that affect it. It also varies among Moving Image, Static Image and Coloured Image after all the senses merge together to create that image. This fusion also reflected reality through the techniques of Art and Aesthetics and through cohesion and coordination. All this was created in a new form of an interesting image. This paper also shows the contribution of sense image in displaying truth and even going to the depths of truth and in the personal manifestation of the poet, and in reflecting the social problems of his age as well. This paper comes to the conclusion that the poet was able to free colour from just being a sense impression, and from its isolated vision. The poet has designated colour's job within the general, so it is not to be viewed as a personal identity and not to be judged independently. It changed from an element of form to one element of meaning's elements, and from its decorative position as a tool of decoration to its role as a tool of expressing feelings.